Implementasi Prinsip Maqashid Syariah Dalam Operasional Perbankan Syariah - Diana Puspita Sari; Anggun Okta Fitri; Muhammad Iqbal Fasa (Inflasi : Jurnal Ekonomi, Manajemen dan Perbankan, 2025)
Maqashid Sharia is a fundamental principle in Islamic law that aims to ensure the welfare of humanity by protecting five important aspects, namely religion (hifdz al-din), soul (hifdz al-nafs), reason (hifdz al-aql), descendants (hifdz al-nasl), and property (hifdz al-maal). In the world of Islamic banking, this principle is the basis for ensuring that all products and services offered not only prioritize financial gain, but also provide broader social benefits to society. The implementation of maqashid sharia in Islamic banking is reflected in the development of partnership-based financial products such as mudarabah and musyarakah. Both of these products allow for a fair sharing of risks and profits between the bank and the customer. In addition, Islamic banks also manage social funds such as zakat, infaq, sedekah, and waqf, which are used to improve the welfare of society more broadly. These principles seek to create a financial system that is fair, transparent, and beneficial to society. However, although the implementation of maqashid sharia has brought positive changes in sharia banking, there are still challenges that need to be faced, such as inadequate regulations and the lack of public understanding of sharia products. Therefore, stronger collaboration between sharia financial institutions and various other stakeholders is needed to maximize the implementation of maqashid sharia and achieve overall welfare of the people